Active compounds and derivatives of camellia sinensis responding to erosive attacks on dentin - Vanara Florêncio Passos; Mary Anne Sampaio de Melo; Juliana Paiva Marques Lima; Felipe Franco Marçal; Cecília Atem Gonçalves de Araújo Costa; Lidiany Karla Azevedo Rodrigues; Sérgio Lima Santiago (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract This research explored the potential of Camellia sinensis-derived teas and active compounds to be used as treatments to prevent dentin wear. Human root dentin slabs were randomly assigned to 5 groups (n = 10) as follows: distilled water (DW, control), epigallocatechin-3-gallate (EGCG), theaflavin gallate derivatives (TF), commercial green tea (GT), and commercial black tea (BT). The samples were submitted to a pellicle formation and an erosive cycling model (5x/day, demineralization using 0.01 M hydrochloric acid/60 s) followed by remineralization (human stimulated saliva/60 min) for three days. The samples were treated for 5 min using the test group solutions between the erosive cycles. Dentin changes were assessed with profilometry analysis and FT-Raman spectroscopy. The data regarding wear were analyzed by ANOVA followed by Tukey's test (p < 0.05). EGCG, TF derivatives, and both regular teas significantly suppressed erosive dentin loss (38-47%, p < 0.05). No obvious changes in the Raman spectra were detected in the specimens; however, the DW group had a minor relationship of 2880/2940 cm−1. The phenolic contents in both green and black tea and the important catechins appear to have protective effects on dentin loss.